Actin-based force generation and cell adhesion in tissue morphogenesis - Clarke, D Nathaniel; Martin, Adam C (Current biology, 2021)
The generation of organismal form - morphogenesis - arises from forces produced at the cellular level. In animal cells, much of this force is produced by the actin cytoskeleton. Here, we review how mechanisms of actin-based force generation are deployed during animal morphogenesis to sculpt organs and organisms. Furthermore, we consider how cytoskeletal forces are coupled through cell adhesions to propagate across tissues, and discuss cases where cytoskeletal force or adhesion is patterned across a tissue to direct shape changes. Together, our review provides a conceptual framework that reflects our current understanding of animal morphogenesis and gives perspectives on future opportunities for study.